Proceedings of the 13th ACM Conference on Electronic Commerce 2012
DOI: 10.1145/2229012.2229077
|View full text |Cite
|
Sign up to set email alerts
|

Supply-limiting mechanisms

Abstract: Most results in revenue-maximizing mechanism design hinge on "getting the price right" -offering to sell a good to bidders at a price low enough to encourage a sale, but high enough to garner non-trivial revenue.Getting the price right can be hard work, especially when the seller has little or no a priori information about bidders' valuations. Moreover, this approach becomes prohibitively challenging when there are multiple indivisible goods on the market, in which case getting the prices right is a long-stand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 26 publications
0
31
1
Order By: Relevance
“…For example, previous work has demonstrated that auctions with reasonably good approximation factors are possible with minimal dependence on the valuation distributions (e.g. [9,26,2]) or even, when there is no bidder with a unique valuation distribution, with no dependence on the valuation distributions [17,18,36]. Another interpretation of some previous results, such as [11,9], is the existence of constant-factor approximate auctions that derive no benefit from bidder competition.…”
Section: Our Resultsmentioning
confidence: 90%
“…For example, previous work has demonstrated that auctions with reasonably good approximation factors are possible with minimal dependence on the valuation distributions (e.g. [9,26,2]) or even, when there is no bidder with a unique valuation distribution, with no dependence on the valuation distributions [17,18,36]. Another interpretation of some previous results, such as [11,9], is the existence of constant-factor approximate auctions that derive no benefit from bidder competition.…”
Section: Our Resultsmentioning
confidence: 90%
“…However, it is easy to see there are instances in which the revenue in every competitive equilibrium is 0 (even for unit-demand valuations). A natural approach to revenue extraction is limiting the supply, which has the effect of increasing competition among the consumers [Roughgarden et al, 2012]. However, recall we are dealing with markets that are unstable unless they clear; bundling should thus be done carefully to ensure market clearance.…”
Section: Revenue Maximizationmentioning
confidence: 99%
“…Recently, several prior-independent auctions were studied [e.g. 8,19,10]. These auctions greatly reduce the amount or precision of the knowledge needed by the auctioneer on the prior distribution, while guaranteeing nearly optimal performance against the fully knowledgeable optimal auction.…”
Section: Introductionmentioning
confidence: 99%